Comparison of UV spectrometry and fluorometry-based methods for quantification of cell-free DNA in red cell components - Khetan, Dheeraj (Asian J Transfus Sci, 2019)
BACKGROUND: Stress and shear force applied on blood components during processing and storage may induce cellular damage leading to release of cell-free DNA (cfDNA). In this study, we have compared ultraviolet (UV) spectrophotometry with UV-induced fluorescence for the quantification of cfDNA in red cell supernatant. MATERIALS AND METHODS: cfDNA was extracted from 200 μL sample of supernatants from 99 packed red blood cells using QIAamp DNA Blood Mini Kit (Qiagen, Germany). Quantification of cfDNA was done using two different methods: one based on spectrophotometry (NanoDrop 2000c, ThermoFisher Scientific, USA) and another based on fluorometry (Qubit 2.0, Life Technologies, ThermoFisher Scientific, USA). Interassay variability of both the methods was estimated using serial dilutions of standard with known DNA concentration. RESULTS: DNA quantification by both the methods was close to actual amount of known standard in dilutions with higher concentration of DNA (21.68 to 2.71 ng/μl). While at higher dilutions, quantification by NanoDrop was neither precise nor accurate. Median cfDNA concentration in the study units was found to be 1.60 ng/μl (25(th)–75(th) percentile range: 1.10–2.10) by UV spectrophotometry (NanoDrop) compared to 0.080 ng/μl (25(th)–75(th) percentile range: 0.050–0.130) by fluorometry (Qubit). CONCLUSION: Due to high interassay variability between the two methods and the better precision and accuracy of Qubit, it is recommended that fluorometry-based method be used for the quantification of cfDNA in blood components.